2003
DOI: 10.1016/s0895-7061(02)03262-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of abnormal nocturnal blood pressure fall on vascular function

Abstract: Microalbuminuria, an index of vascular function, differentiates reverse dippers from nondippers, but not extreme dippers from dippers among hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 22 publications
4
20
0
3
Order By: Relevance
“…Additionally, reverse dippers have been shown to have significantly more Dipper status and arterial stiffness Jerrard-Dunne 1237 Pulse wave velocity according to night : day blood pressure ratio categorized into 5% bands rather than arbitrary definitions. microalbuminuria, an index of vascular function [22]. Furthermore, the observed J-shaped relationship between PWV and dipper status in this study mirrors that observed between dipper status and the incidence of both silent cerebral infarcts and clinical stroke [15].…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, reverse dippers have been shown to have significantly more Dipper status and arterial stiffness Jerrard-Dunne 1237 Pulse wave velocity according to night : day blood pressure ratio categorized into 5% bands rather than arbitrary definitions. microalbuminuria, an index of vascular function [22]. Furthermore, the observed J-shaped relationship between PWV and dipper status in this study mirrors that observed between dipper status and the incidence of both silent cerebral infarcts and clinical stroke [15].…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that nocturnal BP is superior than awake BP as a prognostic predictor of cardiovascular morbidity and mortality in both normotensive and hypertensive individuals [5,6] and that a blunted fall in night-time BP may be related to an increase in target organ damage and cardiovascular events [7][8][9][10]. The clinical and prognostic value of the nondipping pattern, defined as a decline in nocturnal BP less than 10% compared to daytime values [11], however, remains a source of controversial debate as the association between nondipping status and excess of organ damage or cardiovascular events reported by previous studies has not been confirmed by others [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Those fi ndings have been confi rmed recently by Ivanovic et al [68]. Patients with abnormal diurnal BP variation patterns (non-dippers, extreme dippers and reverse dippers) have also showed higher plasma BNP levels than those with normal BPV [69] and reverse dippers had higher microalbumin and micoglobulin excretion, and albumin/creatinine ratio [70].…”
Section: Mechanism Explanationmentioning
confidence: 57%